Valor de las harinas de camote y achiote en raciones para aves de corral - Squibb, R. L.; Méndez, J; Scrimshaw, N.S. (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
In experiments carried out in Guatemala, corn was substituted by sweet potato and achiote (Bixa orellana) in poultry rations. Sweet potatoes substituted satisfactorily; both half and all the corn in the basic ration for baby chicks (16 and 32 per cent of the ration). Although a small decrease in growth was observed in the baby chicks fed the higher level, the difference was not statistically significant. Achiote meal can substitute from 30 to 50 per cent of the corn in baby chicks rations. When all the corn was substituted, a decrease in the rate of growth was observed. In an experiment with laying hens, 3 per cent of achiote meal in the ration increased the carotenoid content in the eggs and improved the yolk color. At the same time, the levels of carotenoids and vitamin A content of the blood serum of the hens increased. The achiote meal remaining after the carotene and bixene had been removed by aqueous extraction for the manufacture of these two concentrates was a good source of vitamin A activity for poultry